Challenges and Strategies: Willingness to Pay for Mangrove Forest Ecotourism Development In Indonesia - Musliha, Cici; Waridin, Waridin; Prastyadewi, Made Ika; Wardhani, Arisanti Ayu; Pratama, Irfandi (E-Journal of Tourism; Volume 10 Number 2 (September 2023)DO - 10.24922/eot.v10i2.101646, 2023)
This study aims to analyze the community's willingness to pay (WTP) and formulate a strategy for developing mangrove forest ecotourism. This study uses a mixed method with a sampling method using accidental sampling of as many as 155 respondents and purposive sampling of as many as seven key people. The results showed that as many as 89% of respondents stated they were willing to spend some money with a total WTP value of US$ 23894.46/year. Most of them have WTP because they believe ecotourism development can increase their income and create them. The total value of WTP can be used as a reference in determining ecotourism entrance tickets. The results of the study suggest strategies that can be done for ecotourism development are to increase supporting facilities, carry out conservation efforts, and increase synergies between stakeholders.